BECOMING CHOLGUEROS An archaeology of the 18th-20th centuries in the Chonos archipelago of Western Patagonia (Chile) - Reyes, Omar; Nuevo Delaunay, Amalia (My University, 2022)
This article discusses the archaeological record of occupations associated with the extraction of coastal resources during the late 18th to early 20th centuries in the Chonos Archipelago (43 degrees 50'-46 degrees 50' S, Patagonia, South America). The characteristics of its occupation by Creole/European groups known as Cholgueros have not yet been archeologically addressed. Cholgueros occupations originated intensely over short periods of time and specialised in the extraction of primary coastal resources for the canned food industry. They are composed of large accumulations of unfragmented, uncompacted, and nonstratigraphic shells of a small number of species of mollusks of commercial value, such as Mytilus. Intertidal management areas are also recorded on these sites, such as stone corrals and boatyard or rock clearance areas to prevent boats from hitting intertidal stones. Due to the reduced time scale of formation of these sites they are sensitive to frequent coastal geomorphological changes and therefore sedimentary witnesses to regional coastal dynamics. The analysis of the Cholgueros sites' evidence broadens our knowledge on coastal use in history, thus allowing us to understand the long timescale of human occupation of the area.
Keywords: western patagonian channels; shell middens; historical archaeology; 18th-20th centuries; cholgueros sites